Ab initio study of electronic and optical properties of penta-SiC2 and -SiGeC4 monolayers for solar energy conversion. (June 2020) - Bouziani, I.; Haman, Z.; Kibbou, M.; Benhouria, Y.; Essaoudi, I.; Ainane, A.; Ahuja, R.
Abstract: In the current study, we explore theoretically electronic and optical properties of penta-SiC2 and -SiGeC4 monolayers based on ab initio computations and utilizing modified Becke–Johnson generalized gradient-approximation (mBJ-GGA) within the density functional theory. The calculated results show that both 2D penta-SiC2 and -SiGeC4 are structurally stable, according to their negative formation energy. Furthermore, we have found that the penta-SiC2 and -SiGeC4 semiconductors show indirect and moderate band gaps of 1.75 and 1.62 eV by employing mBJ-GGA functional, respectively. Also, these systems present sigma- and pi-bond between two nearest neighbor carbon atoms by overlapping sp 2 -sp 2 and p-p orbitals, respectively, as well as an ionic bond between two nearest neighbor Si-C and Ge-C atoms. Additionally, we have shown that the considered compounds exhibit small reflectivity and high absorption peaks in visible region with the shift of absorption edge of 2D penta-SiGeC4 to the low energy visible region due to its small band gap compared to that of 2D penta-SiC2 . These findings make both penta-SiC2 and -SiGeC4 monolayer semiconductors promising candidates for photovoltaic technology. Highlights: Penta-SiC2 and -SiGeC4 monolayers are structurally stable. Penta-SiC2 and -SiGeC4 compounds are indirect semiconductors with moderate bandgaps. Penta-SiC2 and -SiGeC4 systems have small reflectivity and high absorption in visible region. Penta-SiC2 and -SiGeC4 monolayer semiconductors are suitable for photovoltaic technology.